The dawn of the Middle Palaeolithic in western Central Asia: Sel'Ungur Cave in Kyrgyztan - Andrey Krivoshapkin; Bence Viola; Temerlan Chargynov; Maciej T. Krajcarz; Magdalena Krajcarz; Stanisław Fedorowicz; Vladimir Olenchenko; Leonid Tsibizov; Svetlana Shnaider; Kseniya Kolobova (UISPP Journal)
The Sel’Ungur Cave plays a crucial role in our understanding of the initial occupation of Central Asia. During the field campaign of 2014-1016, the techno-complex characterized by the non-Levallois flake knapping and a production of plano-convex bifaces has been recovered. Investigations of Sel’Ungur Cave in 2017 have provided new preliminary data on the earliest stages of Western Central Asia occupation, probably by Neanderthals.